2012
DOI: 10.1111/ans.12031
|View full text |Cite
|
Sign up to set email alerts
|

Creating change: building the capacity of the medical workforce in Aboriginal health

Abstract: Background: This paper provides an overview of the long-term strategies that have been in place at the University of Western Australia, which aim to build the capacity and preparedness of the health-care workforce in Aboriginal health. In 1996, the Centre for Aboriginal Medical and Dental Health was established within the Faculty of Medicine, Dentistry and Health Sciences to implement a comprehensive approach to Aboriginal health. Methods: The initial focus was on developing recruitment and retention strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Half ( n = 13) of the studies focused on issues affecting nursing and midwifery students [11, 28, 34, 4853, 55, 57, 60, 62], five studies focused on medical students [45, 47, 58, 59, 64], three focused on psychology students [43, 56, 63], one study focused on public health students [20], and four studies reported on issues affecting Indigenous students across several health disciplines (courses included: dentistry, health science, human movement, medicine, nursing and midwifery, occupational therapy, physiotherapy and podiatry) [44, 46, 54, 61]. No articles reported specifically on the retention of dental students or any of the other allied health courses (such as social work or physiotherapy) apart from psychology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half ( n = 13) of the studies focused on issues affecting nursing and midwifery students [11, 28, 34, 4853, 55, 57, 60, 62], five studies focused on medical students [45, 47, 58, 59, 64], three focused on psychology students [43, 56, 63], one study focused on public health students [20], and four studies reported on issues affecting Indigenous students across several health disciplines (courses included: dentistry, health science, human movement, medicine, nursing and midwifery, occupational therapy, physiotherapy and podiatry) [44, 46, 54, 61]. No articles reported specifically on the retention of dental students or any of the other allied health courses (such as social work or physiotherapy) apart from psychology.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles emphasised the importance of selecting students through a culturally appropriate interview process [60, 64]. The importance of offering multiple pathways into medicine was also stressed [58, 59, 61, 64].…”
Section: Resultsmentioning
confidence: 99%
“…Once at university, students are supported with tutorial and study help during their university courses. This programme currently has 26 students studying medicine, 2 studying dentistry and 12 studying other health sciences …”
Section: Australiamentioning
confidence: 99%
“…1 The increasing life expectancy and the increasing proportion of elderly patients in trauma centres are well documented. 2 The prevalence of traumatic deaths has rapidly decreased during the last 30 years.…”
Section: Severe Trauma In Elderly Patientsmentioning
confidence: 99%
“…This programme recognizes that students arriving at UWA may not have the subject prerequisites or study skills to initially manage a medical degree and uses bridging and certificate courses to address this. 1 In contrast, the University of Auckland has concentrated on final year secondary school students and developed an admissions policy that recognizes Maori or Pacific cultural competence. Assessment of the students at entry identifies those who have met requirements to enter formal degree courses and those in whom an initial certificate or bridging course may be appropriate.…”
mentioning
confidence: 99%